PENGARUH PENDEKATAN RME BERBANTUAN GEOBOARD TERHADAP PEMAHAMAN KONSEP MATEMATIS PADA MATERI BANGUN DATAR - Pebrianti Nuralsa, Selma; Irawati , Riana; Isrok'atun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the low ability of students to understand mathematical concepts in the material of plane figures. Students still have difficulty in understanding the concepts learned because the choice of learning approaches is not appropriate. The implementation of learning has not focused students to reconstruct their own knowledge, so there is a need for innovation in learning to improve the ability to understand mathematical concepts. This research was conducted to determine the effect of the RME approach assisted by geoboard on students' ability to understand mathematical concepts in the material of plane figures. This research is a quasi-experimental research with a non-equivalent control-group design. The population in this study were all fourth-grade elementary school students in Paseh District. Using a purposive sampling technique, SD Negeri Paseh 1 was selected as the experimental class and SD Negeri Cileuksa as the control class. The instruments used was mathematical concept understanding questions. Based on the research results, the average increase in pretest to posttest results for the experimental class was 38.5 while the control class was 29.89. The RME approach assisted by geoboard has a positive influence on the ability to understand mathematical concepts with an N-Gain value of 0.62. Likewise, the conventional approach has a positive influence on the ability to understand mathematical concepts with an N-Gain value of 0.45. In this case, there is a difference in the influence of the geoboard-assisted RME approach and conventional learning on students' ability to understand mathematical concepts.